2004
DOI: 10.1140/epja/i2004-10055-3
|View full text |Cite
|
Sign up to set email alerts
|

On kaonic deuterium. Quantum field-theoretic and relativistic covariant approach

Abstract: We study kaonic deuterium, the bound K − d state A Kd . Within a quantum field theoretic and relativistic covariant approach we derive the energy level displacement of the ground state of kaonic deuterium in terms of the amplitude of K − d scattering for arbitrary relative momenta. Near threshold our formula reduces to the wellknown DGBT formula. The S-wave amplitude of K − d scattering near threshold is defined by the resonances Λ(1405), Σ(1750) and a smooth elastic background, and the inelastic channels K − … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 35 publications
4
55
0
Order By: Relevance
“…For the S-wave amplitude of K − N scattering near threshold, computed in [1,6], the energy level displacement of the ground state of kaonic hydrogen obtained by Meißner et al [3] is equal to −ǫ This agrees well with both our theoretical result (1.1) and experimental data (1.2) within 1.5 standard deviations for the shift and one standard deviation for the width. In this paper we compute the energy level displacement of the excited np states of kaonic hydrogen, where n is the principal quantum number and p corresponds to the excited state with ℓ = 1.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…For the S-wave amplitude of K − N scattering near threshold, computed in [1,6], the energy level displacement of the ground state of kaonic hydrogen obtained by Meißner et al [3] is equal to −ǫ This agrees well with both our theoretical result (1.1) and experimental data (1.2) within 1.5 standard deviations for the shift and one standard deviation for the width. In this paper we compute the energy level displacement of the excited np states of kaonic hydrogen, where n is the principal quantum number and p corresponds to the excited state with ℓ = 1.…”
Section: Introductionsupporting
confidence: 89%
“…The S-wave scattering lengths a 0 0 and a 1 0 have been treated as free parameters of the approach. Using our results for the S-wave scattering lengths a 0 0 and a 1 0 [1,6] and keeping leading terms in QCD isospin-breaking and electromagnetic interactions, i.e. accounting for only the contribution of Coulombic photons, we have shown that the numerical value of the energy level displacement of the ns state of kaonic hydrogen, computed by Meißner et al [3], agrees well with both our theoretical prediction [1] and recent experimental data by the DEAR Collaboration [2] within 1.5 standard deviations for the shift and one standard deviation for the width.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is obtained without the specification of the numerical values of the coupling constants g 1 and g 2 and the masses of resonances, but using only physical masses of interacting particles for the calculation of phase volumes. 11) where A = − 6.02 fm is the contribution of the Λ(1405) resonance, calculated for g 1 = 0.91 and m Λ(1405) = 1405 MeV Ref. [1].…”
Section: Introductionmentioning
confidence: 99%
“…Using the results obtained in Section 2 for the S-wave scattering lengths of K − N scattering and in Ref. [11] we recalculate the S-wave scattering length a…”
Section: Introductionmentioning
confidence: 99%